Returns to acquirers of public and subsidiary targets - Jaffe, Jeffrey; Jindra, Jan; Pedersen, David; Voetmann, Torben (Journal of Corporate Finance, 2015)
Prior research documents that acquirers of public targets earn zero or negative announcement period returns, while acquirers of private and subsidiary targets earn positive returns. This finding is clearly important to managers and stockholders of acquirers and targets. We employ a large sample of public and subsidiary targets to test four previously unexamined theories of the return differential: synergy, target financial liquidity, target valuation uncertainty, and target bid resistance. We find that none of the empirical measures related to these four theories explains the return differential. This is surprising, since the theories have generally found empirical support in other financial areas.